Establishing baselines for prebiotic production in controlled environments for applications in space and vertical farming - Alberto Battistelli; Simona Proietti; Gabriele Paglialunga; Michele Mattioni; Filomena Nazzaro; Florinda Fratianni; Giuseppe Colla; Mariateresa Cardarelli; Marta Del Bianco; Stefano Moscatello (Heliyon)
Prebiotics might contribute to astronauts' health in space, yet their production in Bioregenerative Life Support Systems (BLSS) remains largely unexplored. Here, chicory (Cichorium intybus L.) exhibited the most appropriate characteristics among seven candidate species as the ideal crop for space prebiotic production systems. Furthermore, we evaluated chicory's performance under different light intensities (250 μmol m−2 s−1 and 500 μmol m−2 s−1 of photosynthetically active radiation) and growing cycle lengths (76 and 91 days after sowing) to optimize prebiotic production. Our findings reveal chicory's remarkable adaptability to fully controlled growing conditions and its ability to accumulate high levels of inulin in the young taproot, despite the short growing cycle. The length of the growing period influenced the productivity of biomass and inulin, the latter depending more on taproot biomass than on inulin content. A growing area of 6.3 m2 might be sufficient for a daily production of 12 g of inulin, the amount of “native chicory inulin” recognized by EFSA to promote health benefits in humans. These results establish important baselines for prebiotic production in BLSS or Controlled Environment Agriculture (CEA) and may be used to design fully controlled cropping systems for space and Earth based vertical farming facilities.